2018
DOI: 10.1039/c8an01612g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall black phosphorus quantum dots: synthesis, characterization, and application in cancer treatment

Abstract: We synthesized black phosphorus quantum dots with good fluorescence performance and excellent biocompatibility, and highlighted their great potential in the photothermal therapy of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…Nanoparticles are particles with the size range of 1-100 nm, which have drawn attractive scientific attention due to their versatile potential applications in optical, electronic, and biomedical fields. [60][61][62][63][64][65][66][67][68][69] Qian et al [29] reported that Se nanoparticles with an average diameter of ≈3 nm and a narrow size distribution, were successfully fabricated in large quantities by liquid-phase exfoliation using NbSe 2 powders as the source material and N-methyl-2-pyrrolidone (NMP) as the dispersant (Figure 2a). High-resolution transmission electron microscopy (HRTEM) image (Figure 2a, inset) reveals that the as-prepared Se nanoparticles have the characteristic of crystalline lattice planes and the d-spacing is 0.23 nm.…”
Section: D Se Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles are particles with the size range of 1-100 nm, which have drawn attractive scientific attention due to their versatile potential applications in optical, electronic, and biomedical fields. [60][61][62][63][64][65][66][67][68][69] Qian et al [29] reported that Se nanoparticles with an average diameter of ≈3 nm and a narrow size distribution, were successfully fabricated in large quantities by liquid-phase exfoliation using NbSe 2 powders as the source material and N-methyl-2-pyrrolidone (NMP) as the dispersant (Figure 2a). High-resolution transmission electron microscopy (HRTEM) image (Figure 2a, inset) reveals that the as-prepared Se nanoparticles have the characteristic of crystalline lattice planes and the d-spacing is 0.23 nm.…”
Section: D Se Nanoparticlesmentioning
confidence: 99%
“…The fundamental light-matter interaction in nanomaterials can also be probed and understood by Raman spectroscopy. [22,63,157,161,162] Figure 11a shows the typical Raman spectrum of a 15 nm thick Se nanosheet at an angle θ of 45°, where θ is defined as an angle between laser polarization direction and [0001] helical chain direction of a Se nanosheet. Three active Raman photon modes are clearly observed, in good accordance with the previous observations in bulk Se.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Though mechanical exfoliation and liquid phase ultrasonic exfoliation have been recognized as the two popular ones for the nano‐BP preparation, some other methods are still applicable, such as electrochemical exfoliation, solvothermal treatment and so on. In the electrochemical exfoliation, bulk BP and Na 2 SO 4 were used as working electrode and the ionic solution, respectively .…”
Section: Nano‐bp Synthesismentioning
confidence: 99%
“…As displayed in Figure a, bulk BP was subjected to grind treatment and subsequently solvothermal treatment with saturated NaOH‐NMP solution as solvent, achieving BPQDs with ultrasmall size of about 2.1 ± 0.9 nm and good dispersion (Figure b–e). Furthermore, BPQDs exhibited blue‐green fluorescence under the irradiation of UV light of 365 nm, providing great potential for developing novel bioimaging platform and fluorescent sensing technique . In addition, the milling crushing of bulk BP was reported to attain few layered thin BP nanoparticles with the yield of over 60 wt% .…”
Section: Nano‐bp Synthesismentioning
confidence: 99%
“…Because of the unique photophysical properties like brightness, photo‐stability, narrow emission, and broad absorption, quantum dots (QDs) have been extensively exploited for cell tracking, bio‐sensing and imaging in vivo . Nevertheless, such growing applications increased concerns over environmental exposure because of the potential toxicity of QDs.…”
Section: Introductionmentioning
confidence: 99%